Towards a Balanced Whole: The Well-Functioning Family - VanKatwyk, Peter L. (The Journal of pastoral care, 2001)
Counters a preoccupation with the dysfunctional family with a description of healthy family functioning through a balancing process between polar opposites. Constructs a Core Dimensions of Family Functioning assessment diagram, integrating the various perspectives of essential family therapies and culminating in the dimension of a spiritual presence in the family. Emphasizes the competence of families and couples to balance competing demands through a case presentation of a critical family life cycle transition.